Thermoinduced fluorescence quenching resistant metal halide perovskite nanocrystal and preparation method and application thereof
By introducing organic small molecular amines in the metal halide permraloma material, the problem of perplexy osteotic fluorescence is solved at high temperature. Preparation of high -performance LED.
Patent Information
- Application Number
- CN202411459702.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-18
AI Technical Summary
Metal halide perovskite materials are prone to thermal fluorescence quenching at high temperatures, resulting in a decrease in luminescence intensity. The prior art is difficult to effectively solve this problem, especially in electroluminescent LEDs.
By introducing organic small molecular amines in situ in the room temperature and air environment, it is introduced to the metal halide perovskite ore, and its structure and charge transmission performance are regulated to enhance its resistance to high temperature.
This method significantly improves the thermal stability of the metal halide perovskite nanocrystalline. When the luminous strength can still maintain 80-90%of the room temperature when 380K, it can restore the initial emitting intensity after heating and cooling circulation. Light -glowing LED.
Smart Images

Figure CN119371337A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of metal halide perovskite nanocrystals, and in particular to a metal halide perovskite nanocrystal resistant to thermally induced fluorescence quenching, and a preparation method and application thereof. Background Art
[0002] Whether it is photoluminescent or electroluminescent devices, Joule heat cannot be completely avoided during operation, and thermal fluorescence quenching is a common challenge faced by all luminescent materials. 4+ , after the temperature rises from 293 Kelvin (K) to 453K, its photoluminescence (PL) intensity will also decrease by about 25%. Similarly, the traditional unprotected cadmium selenide (CdSe) quantum dots lose up to 80% of their PL intensity after heating from 293K to 400K. Metal halide perovskites, as an emerging semiconductor light-emitting material, show great application potential in the field of luminescence applications due to their spectral tunability, narrow emission linewidth, high fluorescence quantum yield and good solution processability. However, metal halide perovskite materials are not immune to the influence of thermal fluorescence quenching. For example, the PL thermal loss of MAPbBr3 perovskite nanocrystals at a high temperature of 400K can reach 70%, and the PL intensity of CsPbBr3 perovskite nanocrystals at 373K drops by more than 80%.
[0003] There are three main strategies for suppressing thermal fluorescence quenching of perovskite materials in the prior art: one is to integrate cooling and heat dissipation equipment, which often requires adjusting the device architecture and is costly. The other two are to keep the perovskite material away from the backlight source and to wrap a silicon dioxide shell on the surface of the perovskite material. Unfortunately, these two strategies are usually only applicable to down-conversion light-emitting diodes (LEDs), not to electroluminescent LEDs with perovskite materials as active layers. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching. At room temperature and in an air environment, on the basis of the metal halide perovskite of the present invention, the organic small molecule amine of the present invention is in situ introduced to solve the problem of thermally induced fluorescence quenching of the metal halide perovskite material, while maintaining the charge transport performance of the perovskite.
[0005] Another object of the present invention is to provide metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching prepared by the above preparation method.
[0006] Another object of the present invention is to provide applications of the above-mentioned metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching, comprising the following steps:
[0009] Dissolving a formamidine source, a cesium source, and a guanidine source in a liquid organic acid, and then mixing to obtain a precursor solution A; wherein the concentration of formamidine is 0.1 to 0.5 mmol / ml; the molar ratio of formamidine to cesium is 28:3 to 28:10; and the molar ratio of formamidine to guanidine is 14:1 to 14:3;
[0010] Dissolving an organic small molecule amine or an acetate of an organic small molecule amine or a carbonate of an organic small molecule amine in a liquid organic acid to obtain an organic small molecule amine solution; mixing the organic small molecule amine solution with the precursor solution A to obtain a precursor solution B; in the precursor solution B, the molar ratio of formamidine to the organic small molecule amine is 14:1 to 14:7; the organic small molecule amine is phenethylamine, m-fluorophenethylamine, o-fluorophenethylamine, p-fluorophenethylamine, 4-(trifluoromethyl)phenethylamine or 4-(trifluoromethoxy)phenethylamine;
[0011] Lead bromide and tetraoctylammonium bromide are mixed and dissolved in toluene to obtain a lead precursor solution;
[0012] Under room temperature and air atmosphere, the precursor solution B and the lead precursor solution are mixed and stirred, and then the organic ammonium halide solution is added and stirred continuously to obtain a crude solution of perovskite nanocrystals; and separation and purification are performed to obtain perovskite nanocrystals.
[0013] Preferably, the formamidine source is formamidine acetate or formamidine carbonate; the cesium source is cesium carbonate or cesium acetate; and the guanidine source is guanidine carbonate or guanidine acetate.
[0014] Preferably, the liquid organic acid is at least one of oleic acid and caprylic acid.
[0015] Preferably, the organic ammonium halide solution is prepared by the following method: didodecyldimethylammonium bromide and oleylamine bromide are mixed and dissolved in toluene to obtain the organic ammonium halide solution.
[0016] More preferably, in the organic ammonium halide solution, the concentration of didodecyldimethylammonium bromide is 0.008-0.02 mmol / mL, and the concentration of oleylamine bromide is 0.02-0.08 mmol / mL.
[0017] Preferably, in the lead precursor solution, the molar ratio of lead bromide to tetraoctylammonium bromide is 1:2 to 1:5.
[0018] Preferably, the molar ratio of formamidine to cesium is (0.7-0.9):(0.1-0.3); more preferably, the molar ratio of formamidine to cesium is 0.8:0.2.
[0019] The present invention also provides a metal halide perovskite nanocrystal resistant to thermally induced fluorescence quenching, which is prepared by the preparation method of the metal halide perovskite nanocrystal resistant to thermally induced fluorescence quenching.
[0020] Preferably, the metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching have a structural component of (FA / Cs)1PbBr3:GA / x-PEA, wherein FA is a monovalent formamidinium ion, Cs is a monovalent cesium ion, Pb is a divalent lead ion, Br is a monovalent bromide ion, GA is a guanidine ligand, and x-PEA is the organic small molecule amine.
[0021] The present invention also provides an application of the metal halide perovskite nanocrystal resistant to thermally induced fluorescence quenching, characterized in that it is used to prepare an active layer of an electroluminescent or photoluminescent LED.
[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0023] (1) The method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching of the present invention introduces a specific amount of a specific organic small molecule amine ligand of the present invention into the specific perovskite system of the present invention, thereby increasing the thermal activation energy and reducing the exciton-phonon coupling caused by lattice thermal vibration, thereby enhancing the ability to resist thermally induced fluorescence quenching, thereby achieving the purpose of improving the thermal stability of the perovskite nanocrystals.
[0024] (2) The metal halide perovskite nanocrystals resistant to thermal fluorescence quenching of the present invention can maintain 80-90% of the luminescence intensity at room temperature at a temperature of 380 K. Moreover, after undergoing a "heating-cooling" cycle, the luminescence intensity can be fully restored, showing great application prospects in the fields of display and lighting, and are particularly suitable for preparing electroluminescent or photoluminescent LEDs with perovskite materials as active layers.
[0025] (3) The method for preparing metal halide perovskite nanocrystals resistant to thermal fluorescence quenching of the present invention does not use polar solvents and produces high-quality, high-performance carboxamidinium-based metal halide perovskite nanocrystals at room temperature; the organic small molecule amine ligand can regulate the crystallization rate of the perovskite during the synthesis process, thereby controlling the grain size and quality. In addition, the organic small molecule amine ligand can also passivate the defects on the surface of the perovskite grains, reduce the surface lead dangling bonds, and enable the excitons to undergo effective radiation recombination in the core layer, thereby improving the radiation recombination luminescence efficiency. The prepared perovskite nanocrystals have a peak wavelength of 530 nanometers (nm), a half-peak width of only 21nm, and a fluorescence quantum yield of 93%, which can meet the requirements of the Rec.2020 standard for pure green luminescence. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 1 and 2 are the photoluminescence spectrum and UV-visible absorption spectrum of Example 1 of the present invention.
[0027] Figure 2 This is the excitation / photoluminescence spectrum of Example 1 of the present invention.
[0028] Figure 3 This is the X-ray diffraction (XRD) spectrum of Example 1 of the present invention.
[0029] Figure 4 FIG. 5 is a curve showing a change in relative photoluminescence intensity versus temperature in Example 1 of the present invention.
[0030] Figure 5 This is a curve showing a relative photoluminescence intensity variation of Example 1 of the present invention in a temperature increase cycle from 300K to 380K and a temperature decrease cycle from 380K to 300K.
[0031] Figure 6 1 and 2 are the photoluminescence spectrum and UV-visible absorption spectrum of Example 2 of the present invention.
[0032] Figure 7 This is the excitation / photoluminescence spectrum of Example 2 of the present invention.
[0033] Figure 8 This is the X-ray diffraction (XRD) spectrum of Example 2 of the present invention.
[0034] Fig. 9 FIG. 5 is a curve showing a change in relative photoluminescence intensity versus temperature in Example 2 of the present invention.
[0035] Fig.10 This is a curve showing a relative photoluminescence intensity variation of Example 2 of the present invention in a temperature increase cycle from 300K to 380K and a temperature decrease cycle from 380K to 300K.
[0036] Fig.11The photoluminescence spectrum and ultraviolet-visible absorption spectrum of Comparative Example 1 of the present invention are shown.
[0037] Fig.12 It is the excitation / photoluminescence spectrum of Comparative Example 1 of the present invention.
[0038] Fig.13 It is the X-ray diffraction (XRD) spectrum of Comparative Example 1 of the present invention.
[0039] Fig.14 The relative photoluminescence intensity of Comparative Example 1 of the present invention varies with temperature.
[0040] Fig.15 This is a curve showing a relative photoluminescence intensity change of Comparative Example 1 of the present invention in a temperature increase cycle from 300K to 380K and a temperature decrease cycle from 380K to 300K.
[0041] Fig.16 The photoluminescence spectrum and ultraviolet-visible absorption spectrum of Comparative Example 2 of the present invention are shown.
[0042] Fig.17 It is the excitation / photoluminescence spectrum of Comparative Example 2 of the present invention.
[0043] Fig.18 It is the X-ray diffraction (XRD) spectrum of Comparative Example 2 of the present invention.
[0044] Fig.19 The relative photoluminescence intensity of Comparative Example 2 of the present invention varies with temperature.
[0045] Fig. 20 This is a curve showing a relative photoluminescence intensity variation of Comparative Example 2 of the present invention in a temperature increase cycle from 300K to 380K and a temperature decrease cycle from 380K to 300K. DETAILED DESCRIPTION
[0046] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0047] Example 1
[0048] This embodiment provides a phenylethylamine (PEA) modified formamidinium-based metal halide perovskite nanocrystal, the structural components of the nanocrystal material are (FA / Cs)1PbBr3:GA / PEA, and the specific synthesis process is as follows:
[0049] (1) Weigh 83.3 mg of formamidine acetate solid powder, add 4 mL of octanoic acid, dissolve at 140 degrees Celsius (°C), and cool to room temperature to prepare a formamidine source; weigh 65.2 mg of cesium carbonate solid powder, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare a cesium source; weigh 24.2 mg of guanidine carbonate solid powder, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare a guanidine source; weigh 24.2 mg of liquid β-phenylethylamine, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare an amine source; and prepare precursor solution B according to the proportions in Table 1.
[0050] (2) Weigh 183.5 mg of lead bromide and 546.8 mg of tetra-n-octylammonium bromide solid powder, dissolve them in 10 mL of toluene, and stir them thoroughly to obtain a lead precursor solution.
[0051] (3) Weigh 80 mg of oleylamine bromide and 40 mg of didodecyldimethylammonium bromide solid powder and dissolve them in 10 mL of toluene. Stir thoroughly to obtain an organic ammonium halide solution.
[0052] (4) 280 μL of precursor solution B was injected into 2.5 mL of vigorously stirred lead precursor solution. After stirring for 30 seconds, 830 μL of organic ammonium halide solution was added. After stirring for another 2 minutes, a crude perovskite nanocrystal solution was obtained.
[0053] (5) The product obtained in step (4) was mixed with methyl acetate (volume ratio 1:2) and centrifuged for purification at a centrifugal speed of 11000 rpm for 5 min to obtain a lower precipitate, which was redispersed in 1 mL of n-octane and centrifuged at a centrifugal speed of 4000 rpm for 5 min to obtain a supernatant.
[0054] (6) Filter the supernatant obtained in step (5) through a polytetrafluoroethylene filter to obtain a purified metal halide perovskite nanocrystal colloidal solution.
[0055] The photoluminescence spectrum and UV-visible absorption spectrum of the perovskite nanocrystals prepared in this example are as follows: Figure 1 As shown; the excitation / photoluminescence spectrum is shown Figure 2 As shown, the maximum fluorescence emission peak wavelength of perovskite nanocrystals is 530nm, and the fluorescence quantum yield is 92%; X-ray diffraction is as follows Figure 3 shown.
[0056] Figure 4 and Figure 5The stability tests of the relative photoluminescence intensity with temperature change in this embodiment in the heating and heating-cooling cycles are shown. It can be seen that at 380K, its luminescence intensity can still maintain 80% of that at 300K, and has good resistance to thermal fluorescence quenching. After two cycles of heating from 300K to 380K and cooling from 380K to 300K, its luminescence intensity can still recover to the initial 100%, showing excellent thermal stability.
[0057] Table 1. Precursor solution B (unit: μL)
[0058]
[0059] Example 2
[0060] This embodiment provides a meta-fluorophenylethylamine (3-F-PEA) modified formamidinium-based metal halide perovskite nanocrystal, the structure of the nanocrystal material is (FA / Cs)1PbBr3:GA / 3-F-PEA, and the specific synthesis process is as follows:
[0061] (1) Weigh 83.3 mg of formamidine acetate solid powder, add 4 mL of octanoic acid, dissolve at 140 degrees Celsius (°C), and cool to room temperature to prepare a formamidine source; weigh 65.2 mg of cesium carbonate solid powder, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare a cesium source; weigh 24.2 mg of guanidine carbonate solid powder, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare a guanidine source; weigh 27.8 mg of liquid m-fluorophenylethylamine, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare an amine source; and prepare precursor solution B according to the proportions in Table 2.
[0062] (2) Weigh 183.5 mg of lead bromide and 546.8 mg of tetra-n-octylammonium bromide solid powder, dissolve them in 10 mL of toluene, and stir them thoroughly to obtain a lead precursor solution.
[0063] (3) Weigh 80 mg of oleylamine bromide and 40 mg of didodecyldimethylammonium bromide solid powder and dissolve them in 10 mL of toluene. Stir thoroughly to obtain an organic ammonium halide solution.
[0064] (4) 280 μL of precursor solution B was injected into 2.5 mL of vigorously stirred lead precursor solution. After stirring for 30 seconds, 830 μL of mixed organic ammonium halide solution was added. After stirring for another 2 minutes, a crude perovskite nanocrystal solution was obtained.
[0065] (5) The product obtained in step (4) was mixed with methyl acetate (volume ratio 1:2) and centrifuged for purification at a centrifugal speed of 11000 rpm for 5 min to obtain a lower precipitate, which was redispersed in 1 mL of n-octane and centrifuged at a centrifugal speed of 4000 rpm for 5 min to obtain a supernatant.
[0066] (6) Filter the supernatant obtained in step (5) through a polytetrafluoroethylene filter to obtain a purified metal halide perovskite nanocrystal colloidal solution.
[0067] The photoluminescence spectrum and UV-visible absorption spectrum of the perovskite nanocrystals prepared in this example are as follows: Figure 6 As shown; the excitation / photoluminescence spectrum is shown Figure 7 As shown in Figure 2, the maximum fluorescence emission peak wavelength of perovskite nanocrystals is 530nm, and the fluorescence quantum yield is 93%; X-ray diffraction is shown in Figure 2 Figure 8 shown.
[0068] Fig. 9 and Fig.10 The stability tests of the relative photoluminescence intensity with temperature change in this embodiment in the heating and heating-cooling cycles are shown respectively. It can be seen that at 380K, its luminescence intensity can still maintain 90% of that at 300K, showing good resistance to thermal fluorescence quenching. After two cycles of heating from 300K to 380K and cooling from 380K to 300K, its luminescence intensity can still recover to the initial 100%, showing excellent thermal stability.
[0069] Table 2. Precursor solution B (unit: μL)
[0070]
[0071] Comparative Example 1
[0072] This comparative example provides a cesium-based metal halide perovskite nanocrystal modified by phenylethylamine (PEA). The structural components of the nanocrystal material are (Cs / FA)1PbBr3:GA / PEA. The specific synthesis process is as follows:
[0073] (1) Weigh 83.3 mg of formamidine acetate solid powder, add 4 mL of octanoic acid, dissolve at 140 degrees Celsius (°C), and cool to room temperature to prepare a formamidine source; weigh 65.2 mg of cesium carbonate solid powder, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare a cesium source; weigh 24.2 mg of guanidine carbonate solid powder, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare a guanidine source; weigh 24.2 mg of liquid β-phenylethylamine, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare an amine source; and prepare precursor solution C according to the proportions in Table 3.
[0074] (2) Weigh 183.5 mg of lead bromide and 546.8 mg of tetra-n-octylammonium bromide solid powder, dissolve them in 10 mL of toluene, and stir them thoroughly to obtain a lead precursor solution.
[0075] (3) Weigh 80 mg of oleylamine bromide and 40 mg of didodecyldimethylammonium bromide solid powder and dissolve them in 10 mL of toluene. Stir thoroughly to obtain a mixed organic ammonium halide solution.
[0076] (4) 280 μL of precursor solution B was injected into 2.5 mL of vigorously stirred lead precursor solution. After stirring for 30 seconds, 830 μL of mixed organic ammonium halide solution was added. After stirring for another 2 minutes, a crude perovskite nanocrystal solution was obtained.
[0077] (5) The product obtained in step (4) was mixed with methyl acetate (volume ratio 1:2) and centrifuged for purification at a centrifugal speed of 11000 rpm for 5 min to obtain a lower precipitate, which was redispersed in 1 mL of n-octane and centrifuged at a centrifugal speed of 4000 rpm for 5 min to obtain a supernatant.
[0078] (6) Filter the supernatant obtained in step (5) through a polytetrafluoroethylene filter to obtain a purified metal halide perovskite nanocrystal colloidal solution.
[0079] The photoluminescence spectrum and UV-visible absorption spectrum of the perovskite nanocrystals prepared in this comparative example are as follows: Fig.11 As shown; the excitation / photoluminescence spectrum is shown Fig.12 As shown, the maximum fluorescence emission peak wavelength of perovskite nanocrystals is 518nm, and the fluorescence quantum yield is 32%; X-ray diffraction is as follows Fig.13 shown.
[0080] Fig.14 and Fig.15 The stability tests of the relative photoluminescence intensity of the samples of this comparative example in the heating and heating-cooling cycles with temperature changes are respectively shown. It can be seen that at 380K, the luminescence intensity of sample 1 remains 28% of that at 300K. It can be seen that after 2 cycles of heating from 300K to 380K and cooling from 380K to 300K, the luminescence intensity of sample 1 can be restored to 89% of the initial value; at 380K, the luminescence intensity of sample 2 remains 37% of that at 300K. It can be seen that after 2 cycles of heating from 300K to 380K and cooling from 380K to 300K, the luminescence intensity of sample 2 can be restored to 77% of the initial value.
[0081] From the above, it can be seen that in the preparation process of the cesium-based metal halide perovskite nanocrystals in this comparative example, the introduction of phenylethylamine cannot significantly improve its thermal stability.
[0082] Table 3. Precursor solution C (unit: μL)
[0083]
[0084] Comparative Example 2
[0085] This comparative example provides a formamidite-based metal halide perovskite nanocrystal, the structural components of the nanocrystal material are (FA / Cs)1PbBr3:GA, and the specific synthesis process is as follows:
[0086] (1) Weigh 83.3 mg of formamidine acetate solid powder, add 4 mL of octanoic acid, dissolve at 140 degrees Celsius (°C), and cool to room temperature to prepare a formamidine source; weigh 65.2 mg of cesium carbonate solid powder, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare a cesium source; weigh 24.2 mg of guanidine carbonate solid powder, add 2 mL of octanoic acid, dissolve at 140°C, and cool to room temperature to prepare a guanidine source; and prepare precursor solution A according to the proportions in Table 4.
[0087] (2) Weigh 183.5 mg of lead bromide and 546.8 mg of tetra-n-octylammonium bromide solid powder, dissolve them in 10 mL of toluene, and stir them thoroughly to obtain a lead precursor solution.
[0088] (3) Weigh 80 mg of oleylamine bromide and 40 mg of didodecyldimethylammonium bromide solid powder and dissolve them in 10 mL of toluene. Stir thoroughly to obtain a mixed organic ammonium halide solution.
[0089] (4) 280 μL of precursor solution A was injected into 2.5 mL of vigorously stirred lead precursor solution. After stirring for 30 seconds, 830 μL of mixed organic ammonium halide solution was added. After stirring for 5 minutes, a crude perovskite nanocrystal solution was obtained.
[0090] (5) The product obtained in step (4) was mixed with methyl acetate (volume ratio 1:2) and centrifuged for purification at a centrifugal speed of 11000 rpm for 5 min to obtain a lower precipitate, which was redispersed in 1 mL of n-octane and centrifuged at a centrifugal speed of 4000 rpm for 5 min to obtain a supernatant.
[0091] (6) Filter the supernatant obtained in step (5) through a polytetrafluoroethylene filter to obtain a purified metal halide perovskite nanocrystal colloidal solution.
[0092] The photoluminescence spectrum and UV-visible absorption spectrum of the perovskite nanocrystals prepared in this comparative example are as follows: Fig.16 The excitation / photoluminescence spectra are shown in Fig.17 As shown in Figure 2, the maximum fluorescence emission peak wavelength of perovskite nanocrystals is 532nm, and the fluorescence quantum yield is 83%. Fig.18 shown.
[0093] Fig.19 and Fig. 20 The relative photoluminescence intensity of the comparative example is tested for stability with temperature changes in the heating and heating-cooling cycles. It can be seen that at 380K, its luminescence intensity maintains 70% of that at 300K, showing better resistance to thermal fluorescence quenching compared with Examples 1 and 2. After two cycles of heating from 300K to 380K and cooling from 380K to 300K, its luminescence intensity can be restored to 90% of the initial value, showing poor thermal stability compared with Examples 1 and 2.
[0094] Table 4. Perovskite precursor solution A formula (unit: μL)
[0095]
[0096]
[0097] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching, characterized in that: The following steps are involved: Dissolving a formamidine source, a cesium source, and a guanidine source in a liquid organic acid, and then mixing to obtain a precursor solution A; wherein the concentration of formamidine is 0.1 to 0.5 mmol / ml; the molar ratio of formamidine to cesium is 28:3 to 28:10; and the molar ratio of formamidine to guanidine is 14:1 to 14:3; Dissolving an organic small molecule amine or an acetate of an organic small molecule amine or a carbonate of an organic small molecule amine in a liquid organic acid to obtain an organic small molecule amine solution; mixing the organic small molecule amine solution with the precursor solution A to obtain a precursor solution B; in the precursor solution B, the molar ratio of formamidine to the organic small molecule amine is 14:1 to 14:7; the organic small molecule amine is phenethylamine, m-fluorophenethylamine, o-fluorophenethylamine, p-fluorophenethylamine, 4-(trifluoromethyl)phenethylamine or 4-(trifluoromethoxy)phenethylamine; Lead bromide and tetraoctylammonium bromide are mixed and dissolved in toluene to obtain a lead precursor solution; Under room temperature and air atmosphere, the precursor solution B and the lead precursor solution are mixed and stirred, and then the organic ammonium halide solution is added and stirred continuously to obtain a coarse perovskite nanocrystal solution; Separation and purification are carried out to obtain perovskite nanocrystals.
2. The method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching according to claim 1, characterized in that: The formamidine source is formamidine acetate or formamidine carbonate; the cesium source is cesium carbonate or cesium acetate; and the guanidine source is guanidine carbonate or guanidine acetate.
3. The method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching according to claim 1, characterized in that: The liquid organic acid is at least one of oleic acid and caprylic acid.
4. The method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching according to claim 1, characterized in that: The organic ammonium halide solution is prepared by the following method: didodecyl dimethyl ammonium bromide and oleylamine bromide are mixed and dissolved in toluene to obtain the organic ammonium halide solution.
5. The method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching according to claim 4, characterized in that: In the organic ammonium halide solution, the concentration of didodecyl dimethyl ammonium bromide is 0.008-0.02 mmol / mL, and the concentration of oleylamine bromide is 0.02-0.08 mmol / mL.
6. The method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching according to claim 1, characterized in that: In the lead precursor solution, the molar ratio of lead bromide to tetraoctylammonium bromide is 1:2 to 1:
5.
7. The method for preparing metal halide perovskite nanocrystals resistant to thermally induced fluorescence quenching according to claim 1, characterized in that: The molar ratio of formamidine to cesium is (0.7-0.9):(0.1-0.3).
8. A metal halide perovskite nanocrystal resistant to thermally induced fluorescence quenching, characterized in that: The nanocrystal is prepared by the method for preparing the metal halide perovskite nanocrystal resistant to thermal fluorescence quenching as described in any one of claims 1 to 7.
9. The metal halide perovskite nanocrystal resistant to thermally induced fluorescence quenching according to claim 8, characterized in that: Its structural components are (FA / Cs)1PbBr3:GA / x-PEA, wherein FA is a monovalent formamidinium ion, Cs is a monovalent cesium ion, Pb is a divalent lead ion, Br is a monovalent bromide ion, GA is a guanidine ligand, and x-PEA is the organic small molecule amine.
10. The use of the metal halide perovskite nanocrystals resistant to thermal fluorescence quenching according to claim 8 or 9, characterized in that: Used to prepare the active layer of electroluminescent or photoluminescent LED.
Citation Information
Patent Citations
Room-temperature A-site doping method for APbX3 perovskite quantum dots
CN108774157A
Multi-lead oligomer, preparation method and application thereof
CN110218223A
Method for simultaneously improving open-circuit voltage and stability of full-suede perovskite / crystalline silicon laminated solar cell
CN114267789A
Low-defect-state-density methylamine-free perovskite single crystal with synergistic effect of dopant and auxiliary dopant as well as preparation method and application of low-defect-state-density methylamine-free perovskite single crystal
CN115044982A